Polypropylene/Polystyrene Blends: In Situ Compatibilization by Friedel-Crafts Alkylation Reaction - Diaz, Monica Fatima (2004)
The application of Friedel-Crafts alkylation reaction to the compatibilization of polypropylene (PP)/polystyrene (PS) blends was assessed. A PP macrocarbocation is chemically bonded to the PS benzene ring by aromatic electrophilic substitution. The graft copolymer formed at the interphase (PP-g-PS) showed relatively high emulsification strength, suggesting an effective behavior as in situ compatibilizer. The critical micelle concentration (CMC) was related to Friedel-Crafts catalyst concentration. The amount of PS grafting and possible appearance of crosslinking and chain scission side reactions were also analyzed. The reaction products were characterized by a combination of size exclusion chromatography and Fourier transform infrared techniques applied after a careful solvent extraction separation. It was found, from the emulsification curve, that CMC was achieved when 0.7 wt % AlCl3 was added. This value was confirmed by scanning electron microscopy observation of phase adhesion on fractured sample surfaces. Mass balances of extracted PS showed that at least 15 wt % of the initial PS resulted grafted at the CMC condition. Chain scission reactions, in parallel with grafting, were verified to occur for PP as well as for PS. Instead, crosslinking reactions were not detected.